ANTIOXIDANT EFFECT OF FUNCTIONAL CHICKEN NUGGETS UTILIZING KODO MILLET (PAsPAluM scrobiculAtuM) - AN INDIAN NUTRICEREAL - C. Vasanthi,; V. Appa Rao,; R. Narendra Babu,; R. Karunakaran,; S. Ezhilvelan,; R. Ramani,; M. Muthulakshmi, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Antioxidant effect of Kodo millet (Paspalum scrobiculatum) was exploited in the preparation of functional chicken nuggets replacing refined wheat flour at 5% (T1), 6% (T2), 7% (T3) and 10% (T4) levels while control nuggets were prepared using Refined Wheat Flour. Antioxidant potential was assessed by DPPH radical scavenging activity, ABTS radical cation decolourization assay and Ferric Reducing Antioxidant Power. Hunters colour analysis reflected the antioxidant effect of kodo millet in chicken nugget due to the presence of phytochemicals. Incorporation of kodo millet in chicken nuggets had enriched the antioxidant capacity by 8.26% for DPPH radical scavenging activity, 11.43% for ABTS activity, and 36.29% for FRAP activity over control.